2019
DOI: 10.1093/icvts/ivz291
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of mitral valve tenting area in patients with functional mitral regurgitation

Abstract: OBJECTIVES Mitral valve (MV) repair in functional mitral regurgitation is still associated with suboptimal outcomes. Our goal was to determine whether the clinical outcome following MV repair correlates with preoperative tenting parameters. METHODS We retrospectively identified consecutive patients with functional mitral regurgitation who underwent an isolated MV annuloplasty during a 7-year period (2010–2016) from our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our preliminary study showed that nonindexed MV tenting area >2.4 cm 2 was associated with a worse prognosis in patients with FMR following MV repair (HR 2.1; p=0.03). 5 Other researchers investigated also the prognostic value of non-indexed MV tenting area in FMR and found that the cut-off value of MV tenting area predicting adverse clinical outcomes ranged from 2.5 to 3.4 cm 2 (table 4). [6][7][8][9] Moreover, recommendations of European Association of Echocardiography defined non-indexed tenting area >2.5 cm 2 as a risk factor for recurrent MR following MV repair in FMR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our preliminary study showed that nonindexed MV tenting area >2.4 cm 2 was associated with a worse prognosis in patients with FMR following MV repair (HR 2.1; p=0.03). 5 Other researchers investigated also the prognostic value of non-indexed MV tenting area in FMR and found that the cut-off value of MV tenting area predicting adverse clinical outcomes ranged from 2.5 to 3.4 cm 2 (table 4). [6][7][8][9] Moreover, recommendations of European Association of Echocardiography defined non-indexed tenting area >2.5 cm 2 as a risk factor for recurrent MR following MV repair in FMR.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results with a limited follow-up had been previously published by our group. 5 Individual patient consent was waived. Patients or public were not involved in our study design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation